Analysis of Factors Affecting the Success of a Digital Business Franchise Is (Case Study: Warung Pintar in Salatiga City) - Heni Wahyu Susanti; Lieli Suharti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study was conducted with the aim of knowing the description of the smart shop franchise and the factors that influence the success of MSME actors in running a smart shop franchise business in the city of Salatiga, Central Java. The research method used is a qualitative method using descriptive analysis. The technique used in data collection is in -depth interviews. After the data was obtained, it was analyzed using descriptive analysis techniques using a qualitative approach. from the results of the study, the findings show that the smart shop is a MSME business platform to digitize the growth of traders and consumers in Indonesia. By digitizing the distribution system, Warung Pintar is able to create information transparency for all stakeholders and the requirements to build a smart shop franchise such as having a shop, a strategic location and being able to use a smartphone. Service quality factors, motivation, commitment and a strategic location can support the success of a smart shop franchise business. Meanwhile, the benefits of owning a smart shop franchise are: cost-effective, time-efficient, guaranteed stock availability and promotions.